1995
DOI: 10.1093/hmg/4.10.1911
|View full text |Cite
|
Sign up to set email alerts
|

Increased instability of intermediate alleles in families with sporadic Huntington disease compared to similar sized intermediate alleles in the general population

Abstract: We have directly compared intergenerational stability of intermediate alleles (IAs) derived from new mutation families (IANM) for Huntington disease (HD) with IAs in the general population (IAGP) which occur in approximately 1 in 50 persons. Analysis of meiotic events in blood and sperm reveals that IANM are significantly more unstable than IAGP despite similar size. However, for both IANM and IAGP CAG changes were small and risks for inheriting an expansion into the HD affected range were low. Sequence analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
2
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(130 citation statements)
references
References 0 publications
7
120
2
1
Order By: Relevance
“…This multi-step model of the evolution of HD alleles is a generally accepted mechanism for the development of dynamic mutations in Huntington disease as well as in other triplet repeat disorders. This is further supported by the finding that all intermediate alleles (IAs, have an B7 or the A7 haplotypes (as shown in this work and other reports) (Squitieri et al, 1994;Almqvist et al, 1995;Goldberg et al, 1995). Since intermediate alleles present a critical threshold of the CAG repeat size that can undergo massive expansion to the HD range during transmissions through successive generations, special concern should be taken when counseling these individuals.…”
Section: Discussionsupporting
confidence: 85%
“…This multi-step model of the evolution of HD alleles is a generally accepted mechanism for the development of dynamic mutations in Huntington disease as well as in other triplet repeat disorders. This is further supported by the finding that all intermediate alleles (IAs, have an B7 or the A7 haplotypes (as shown in this work and other reports) (Squitieri et al, 1994;Almqvist et al, 1995;Goldberg et al, 1995). Since intermediate alleles present a critical threshold of the CAG repeat size that can undergo massive expansion to the HD range during transmissions through successive generations, special concern should be taken when counseling these individuals.…”
Section: Discussionsupporting
confidence: 85%
“…6,11 The likelihood that transmission of an allele in this range will expand into an HD allele is dependent on several factors, including the sex of the transmitting individual, the size of the allele, the molecular configuration of the region surrounding the CAG repeat, and its haplotype. 11,12 This risk may be as high as 6-10% for paternal alleles carrying a CAG repeat of 35.…”
Section: Guidelines Definition Of Normal and Mutation Categorymentioning
confidence: 99%
“…18 Frequency of large alleles (class 2), among all normal chromosomes in our sample (3.7%), was considerable (although within ranges previously described, if corrected for the same size intervals. 12,19 ) This prompted us to undertake a population study of 2000 control alleles, which showed a similar value (unpublished data). 12 Correlation between age at onset and (CAG) n size (r 2 ¼ 0.49), mean age at onset in HD (43.8 years), and that slightly higher in 'HD-like' patients (46.2 years), was also in accordance with previous studies.…”
Section: Characterisation Of Our Patient Populationmentioning
confidence: 80%